Ecclesiastical Policies on Education: A Democratic Game of Winners and Losers? - Aldrin, Viktor (International journal of practical theology, 2024)
In the post-secular societies of Scandinavia and Great Britain, Christian denominations have had to reconstruct their identities as educational agents. This article focuses on the Church of England and the Church of Sweden, and their changed self-identification as expressed in their educational policy documents. Whereas the Church of England’s discourses are of partnership and business competition, the Church of Sweden’s discourses are about the Apocalypse and external threats. These approaches are analysed using Habermas’s concept of religion, identifying a transformation of religious language into secular argumentation to become viable in the secular public space. The question posed is: "Is theology exerting less influence over education in Scandinavia and Great Britain?"